PROTECT trial - Individual interviews with participants in the intervention group - PROTECT trial - Qualitative interviews - Barenfeld, Emmelie; Ekman, Inger (University of Gothenburg, 2020)
The data material contains transcripts of twelve individual interviews with participants who have participated in a person-centred e-health intervention containing telephone support and access to a digital platform. The interview concerned experiences of the content and design of the intervention, future development of digital services and experiences of using the person-centred support.

Individual interviews.

The individual transcriptions are provided in separate documents. Structural details are provided in a readme file.

Datamaterialet innehåller transkriberingar av 12 individuella intervjuer med deltagare som har haft tillgång till ett personcentrerat stöd via telefon och en digital plattform. Intervjuerna handlar om deras erfarenheter av innehåll och utformning av stödet, tankar om framtida utveckling liksom erfarenheter av att använda stödet.

Individuella djupintervjuer.

Transkriptionerna är inmatade i separata dokument för varje individ. Se readme-fil för övrig tabulatur.
PROTECT - Individuella intervjuer med deltagare i interventionsgruppen - PROTECT RCT - Kvalitativa intervjuer
Keywords: Heart Failure; Hjärtsvikt; Pulmonary Disease, Chronic Obstructive; Kroniskt obstruktiv lungsjukdom; Telemedicine; Telemedicin; Patient-Centered Care; Patientcentrerad vård; Qualitative Research; Kvalitativ forskning; Grounded Theory; Grundad teori; person-centred care; personcentrerad vård; COPD; KOL; Chronic Heart failure; kronisk hjärtsvikt; e-health; e-hälsa; Health Sciences; Hälsovetenskap